Pemberdayaan Masyarakat Pedesaan melalui Penguatan Kelembagaan Lokal dalam Pemasaran Produk Olahan Hasil Pertanian - Imam Santosa (Prosiding University Research Colloquium, 2018)
This research is aimed to formulate empowering local institutions that support the development of marketing by processing products of agricultural product. Research design uses a combination of qualitative and quantitative approaches with a more dominant qualitative way. This research is located in Baturaden Subdistrict, Banyumas Regency and Karangreja District, Purbalingga Regency. Both are in Central Java Province. Based on the research's results revealed, that the design mechanism strengthening local institutions in the marketing of processed agricultural products. Access to technology transfer is an important part. Another element of support in the form of clear linkage between farmers and agro-tourism market managers, while accessibility of price information from processed products is also an essential factor. Another strengthening factor is achieved by strengthening the social relations with a pattern of reciprocity especially in partnership.